2021
DOI: 10.1002/ejoc.202001479
|View full text |Cite
|
Sign up to set email alerts
|

2,3‐Dichloro‐5,6‐dicyano‐1,4‐benzoquinone (DDQ)‐Mediated Tandem Oxidative Annulation for Preparing 2,2‐Disubstituted 2,3‐Dihydroquinazolin‐4(1H)‐ones

Abstract: An efficient tandem oxidative annulation for the synthesis of 2,2‐disubstituted 2,3‐dihydroquinazolin‐4(1H)‐ones via DDQ‐mediated dual cross‐dehydrogenative‐coupling (CDC) reactions is described. This transformation proceeds from easily available o‐aminobenzamides and 1,3‐diarylpropenes under mild conditions, and the corresponding products are obtained in moderate to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…This showed that both termini of the propene core can be functionalized, but variations in the nucleophile structure can deliver products in which the same carbon is functionalized twice. 64 This is seen in the coupling of 76 with amide 82 to yield 83 .…”
Section: Quinone Oxidantsmentioning
confidence: 97%
“…This showed that both termini of the propene core can be functionalized, but variations in the nucleophile structure can deliver products in which the same carbon is functionalized twice. 64 This is seen in the coupling of 76 with amide 82 to yield 83 .…”
Section: Quinone Oxidantsmentioning
confidence: 97%
“…16 Due to the extensive biological properties associated with quinazolinone moieties in drug design, obtaining these compounds is of great relevance and has motivated the development of multiple synthetic strategies such as ring opening of isatoic anhydride by nitrogen nucleophiles followed by the oxidative cyclocondensation by electrophiles, 17 aza-Wittig/cyclization reactions of iminophosporanes, 18 oxidative olefin bond cleavage, 19 transition metal dehydrogenative coupling, 20 transition metal-free dehydrogenative coupling, 21 transition metal-catalyzed cross-coupling, 22 palladium-catalyzed carbonylative methods 23 and miscellaneous transition metal-free methods. 24 Likewise, interest in these compounds has also led to spectroscopic structural studies, and X-ray diffraction analysis of this class of heterocycles. 25 …”
Section: Introductionmentioning
confidence: 99%